Triglavski ledenik - Triglav Čekada, Mihaela (Geografija Slovenije, 2014)
The Triglav Glacier lies on the southeast edge of the Alps, in the Julian Alps below Mount Triglav, Slovenia's highest peak. Its upper edge lies at 2,500 m. The glacier has been regularly measured, observed, and studied since 1946 by the Anton Melik Geographical Institute at ZRC SAZU. When measurements began it covered 14.4 ha, but today it covers less than half a hectare. The glacier no longer has all glacial features. Thus one may only speak of a glacier because of its past, when it clearly had the basic features of an alpine glacier. Analysis of the geomorphic forms of the Triglav Mountains allows reconstruction of past glaciation. Moraine deposits above the upper edge of Mount Triglav's North Wall indicate the glacier's extent during the Little Ice Age. When this ended in the nineteenth century, visits to the Triglav Mountains started increasing, and so there are many written and pictorial sources available from this time.